Determinan Penerimaan Pajak Kendaraan Bermotor Di Pulau Jawa Tahun 2017-2021 - Arta Uli M.P, Denisa; Nairobi; Darmawan, Arif (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2024)
This study aims to determine the effect of the number of motorized vehicles, GRDP in the transportation sector, and GRDP per capita on motor vehicle tax revenue in Java Island. The type of data used in this study is secondary data obtained from the Central Statistics Agency (BPS) website. This study uses multiple linear analysis methods to determine the influence of the variable number of motorized vehicles, GRDP in the transportation sector, and GRDP per capita on motor vehicle tax revenue. The results of this study indicate that the variable number of motorized vehicles and GDP per capita has a positive and significant effect on motor vehicle tax revenue in Java. While the transportation sector GRDP variable has a positive and insignificant effect on motor vehicle tax revenue on the island of Java.